Religious Music According to the Perspective of Ustaz Adi Hidayat and Ustaz Khalid Bassalamah - Aisyah Fitri Nur Hasanah; Nindita Farah Sasmaya; Aullya Anisa’ Fauziah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the differences and similarities between Ustaz Adi Hidayat and Ustaz Khalid Basalamah regarding the Islamic ruling on music. Music is a universal phenomenon that holds not only aesthetic value but also emotional, social, and spiritual influence on human life. In Islamic discourse, debates about the permissibility of music have persisted for centuries, mainly due to the absence of explicit Qur’anic verses that either prohibit or permit it. This research employs a qualitative method with a descriptive-analytical approach to explore the arguments of both scholars from legal (fiqh), social, and cultural perspectives. The findings indicate that Ustaz Adi Hidayat allows music as long as it conveys positive meaning and does not contradict Islamic principles, while Ustaz Khalid Basalamah prohibits music because it may distract believers and harden the heart. Through this comparison, the study seeks to provide a comprehensive understanding of the position of music in Islam and to encourage a balanced attitude in evaluating art through a religious lens.